Evaluation of imputation-based association in and around the integrin-?-M (ITGAM) gene and replication of robust association between a non-synonymous functional variant within ITGAM and systemic lupus erythematosus (SLE) (2009)
We recently identified a novel non-synonymous variant, rs1143679, at exon 3 of the ITGAM gene associated with systemic lupus erythematosus (SLE) susceptibility in European-Americans (EAs) and African-Americans. Using genome-wide association approach, three other studies also independently reported an association between SLE susceptibility and ITGAM or ITGAM-ITGAX region. The primary objectives of this study are to assess whether single or multiple causal variants from the same gene or any nearby gene(s) are involved in SLE susceptibility and to confirm a robust ITGAM association across nine independent data sets (n = 8211). First, we confirmed our previously reported association of rs1143679 (risk allele 'A') with SLE in EAs (P = 1.0 × 10-8) and Hispanic-Americans (P = 2.9 × 10-5). Secondly, using a comprehensive imputation-based association test, we found that ITGAM is one of the major non-human leukocyte antigen susceptibility genes for SLE, and the strongest association for EA is the same coding variant rs1143679 (log10Bayes factor=20, P = 6.17 × 10-24). Thirdly, we determined the robustness of rs1143679 association with SLE across three additional case-control samples, including UK (P = 6.2 × 10-8), Colombian (P = 3.6 × 10-7), Mexican (P = 0.002), as well as two independent sets of trios from UK (P TDT = 1.4 × 10-5) and Mexico (P TDT = 0.015). A meta-analysis combing all independent data sets greatly reinforces the association (P meta = 7.1 × 10-50, odds ratio = 1.83, 95% confidence interval = 1.69-1.98, n = 10 046). However, this ITGAM association was not observed in the Korean or Japanese samples, in which rs1143679 is monomorphic for the non-risk allele (G). Taken together along with our earlier findings, these results demonstrate that the coding variant, rs1143679, best explains the ITGAM- SLE association, especially in European- and African-derived populations, but not in Asian populations. © The Author 2009. Published by Oxford University Press. All rights reserved.